Asian dust transport during the last century recorded in Lake Suigetsu sediments. Issue 6 (24th March 2016) - Nagashima, Kana; Suzuki, Yoshiaki; Irino, Tomohisa; Nakagawa, Takeshi; Tada, Ryuji; Hara, Yukari; Yamada, Kazuyoshi; Kurosaki, Yasunori
Abstract: Asian dust has a significant impact on the natural environment. Its variability on multiple timescales modulates the ocean biogeochemistry and climate. We demonstrate that temporal changes in the deposition flux of Aeolian dust recorded in sediments from Lake Suigetsu, central Japan, during the last century exhibit a continuous decreasing trend and a decadal‐scale decrease in 1952–1974. The former decreasing trend can be explained by a decrease in the dust storm frequency at source regions due to the warming of Mongolia in the twentieth century, suggesting future decrease of Asian dust transport with further warming in Mongolia. Decadal‐scale decrease of Aeolian dust is explained by weaker westerlies in lower latitudes in central Japan, reflecting a weaker Aleutian Low during the corresponding period. Decadal‐scale westerly change probably causes north–south shifts of the dominant dust transport path, which affects subarctic northern Pacific Ocean biogeochemistry by changing the micronutrient iron supply. Key Points: Asian dust flux is determined using a lake sediment core from Japan Dust flux shows a decreasing trend with the warming of Mongolia Decadal decrease in dust flux represents northward shift of the westerly